2 - The Challenge of Drug Trafficking to Democratic Governance and Human Security in West Africa: A Historical Reflection - Ogunniyi, Olayemi Jacob; Akpu, James Onochie (Africa Development, 2019)
We argue that West Africa has come into the spotlight as an increasingly important site and destination in the global drug trafficking system. Evidence of the growing role of the sub-region in the global strategy and operations of international drug cartels is broad and varied, comprising a complex admixture of both direct, traceable facts from official and non-official sources, and more indirect information of an indicative, associative and anecdotal nature. Initially targeted as a re-distribution centre and transit point for the trafficking of drugs to end-use destinations around the world, most notably Europe and North America, the sub-region has gradually become a market destination in its own right for global drug cartels mainly, though not exclusively, originating from Latin America. Evidence also points to the emergence of West Africa as an increasingly significant production site for some types of drugs, including amphetamine-type stimulants. The analysis presented in this article points to the history and context of the governance and human security challenges faced by West African countries and the ways in which drug trafficking cartels have both taken advantage of them and, simultaneously, contributed to the exacerbation of the problems. The article concludes that in responding to the governance challenges posed by or associated with drug trafficking, West African countries, working together with one another and in concert with Western countries, civic groups/movements and the private sector will need a much more coherent and coordinated approach, anchored on the idea of the ultimate indivisibility of governance and human security in the sub-region.